2023
DOI: 10.3390/su15075918
|View full text |Cite
|
Sign up to set email alerts
|

Response of Growth-Related Traits of Submerged Macrophytes to Light Reduction: A Meta-Analysis

Abstract: Underwater light reduction is presumably becoming more frequent and intensified due to eutrophication and algal blooms, which may significantly affect submerged macrophytes’ growth. However, a comprehensive understanding of how light reduction influences growth-related traits and responses is currently lacking. Here, we compiled data from 333 records of 62 published works that used controlled experiments to explore the responses of functional traits associated with growth to light reduction. Our results indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 105 publications
0
3
0
Order By: Relevance
“…A previous study suggested that light conditions could explain as much as 77% of the variation in macrophyte presence frequency [56]. Based on a meta-analysis, Gao et al (2023) [57] showed that the effect of light reduction on the growth rate of submerged macrophytes existed at a threshold value (c. 20%). Namely, slight light reduction promoted, but more than 20% light reduction inhibited the growth of submerged macrophytes.…”
Section: Lightmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study suggested that light conditions could explain as much as 77% of the variation in macrophyte presence frequency [56]. Based on a meta-analysis, Gao et al (2023) [57] showed that the effect of light reduction on the growth rate of submerged macrophytes existed at a threshold value (c. 20%). Namely, slight light reduction promoted, but more than 20% light reduction inhibited the growth of submerged macrophytes.…”
Section: Lightmentioning
confidence: 99%
“…Light affects the growth and distribution of submerged macrophytes mainly via photosynthesis, metabolism, and the rhizosphere microbial community [57]. First, low light decreases the photosynthesis rate, and then carbon assimilation decreases.…”
Section: Lightmentioning
confidence: 99%
See 1 more Smart Citation